1973
DOI: 10.1104/pp.51.4.708
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Formation of Amylases and Proteases in the Cotyledons of Germinating Peas

Abstract: Protease activity increased in attached cotyledons of germinated peas (Pisum sativum L. cv. Alaska) as the stored proteins declined but did not increase in excised cotyledons incubated for the same length of time. Cotyledons of seeds germinated in the presence of a casein hydrolysate solution developed less protease activity than did those germinated on water. These results suggest that accumulation of amino acids regulates the protease level in the cotyledons of germinating peas.In contrast to protease, a-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
56
1

Year Published

1977
1977
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 15 publications
8
56
1
Order By: Relevance
“…Incorporation of [3H~leucine into protein and a-amylase was investigated at various stages of germination and incubation (Table I) (13) and pea (26). These findings support the concept that proteolytic activity is mainly involved in the regulation of cotyledonary a-amylase fluctuation, and the proteolytic activity may be controlled by the existence of axis organs or hormonal action.…”
Section: Methodssupporting
confidence: 56%
See 1 more Smart Citation
“…Incorporation of [3H~leucine into protein and a-amylase was investigated at various stages of germination and incubation (Table I) (13) and pea (26). These findings support the concept that proteolytic activity is mainly involved in the regulation of cotyledonary a-amylase fluctuation, and the proteolytic activity may be controlled by the existence of axis organs or hormonal action.…”
Section: Methodssupporting
confidence: 56%
“…Many studies on effects of axis removal or plant hormones have been done, but there are some discrepancies. For example, Yomo and collaborators (24,26) reported that a-amylase activity increases in the cotyledons during seedling growth and during incubation of axisfree cotyledons of pea and bean. This was inconsistent with the findings of others that this increase is partially inhibited by axis removal (3,11,23 processes of seed formation between cereal and leguminous seeds (2), we studied the mechanism of a-amylase formation in cotyledons of germinating bean seeds.…”
mentioning
confidence: 99%
“…A number of researchers have used pea seeds for their experiments, but contradictory results have been reported, possibly because the experimental conditions were not standardized. In the case of a-amylase activity, the consequences of excision of cotyledons include inhibition (6,13), promotion (15), and no appreciable effect (1). A reason for these contradictory results is reported.…”
mentioning
confidence: 99%
“…In contrast, in legume seeds, the mechanism for the development of a-amylase is much less clear; hormonal control of a-amylase development such as seen in cereals has not been demonstrated unambiguously. Although much work has been done on the role of the embryonic axis in the development of the enzyme in reserve tissues (cotyledon), the results are inconsistent (6,10,12,19,20).In a previous report (1 1 no dicot amylase cDNA has been available. In the present study we have cloned cDNA for mung bean a-amylase and examined the levels of a-amylase transcript in cotyledons.…”
mentioning
confidence: 91%